The effect of treffinger learning model on problem solving ability viewed from students logical mathematical intelligence - Putu Umi Kartika Dewi; Gusti Ayu Mahayukti; I Gusti Putu Sudiarta (STKIP PGRI Banjarmasin, 2019)
The problem-solving abilities of students were still low because students have not been able to develop their creativity in problem-solving so that a Treffinger learning model is needed by paying attention to students logical- mathematical intelligence. The purpose of this study was at examining the effect of the Treffinger learning model on mathematical problem-solving ability viewed students from logical-mathematical intelligence. The instrument used in this study was logical-mathematical intelligence tests and mathematical problem-solving tests. This study used treatment by level design and the population of this study was X MIPA class of SMA Negeri 2 Singaraja. The sample of this study was determined by using cluster random sampling technique. The data obtained were analysed using a two-way analysis of variance (ANOVA). The result of the study showed that the mathematical problem-solving ability of students who followed the Treffinger learning model is higher than students who followed the conventional learning model. There is an interaction between the learning model and logical-mathematical intelligence towards mathematical problem-solving ability. Students who have high logical-mathematical intelligence are more suitable followed the Treffinger learning model, on the other hand, students who have low logical-mathematical intelligence are more suitable followed conventional learning.